Synthesis, antimalarial activity, structure–activity relationship analysis of thieno-[3,2-b]benzothiazine S,S-dioxide analogs - Barazarte, Arthur (2008)
An improved procedure for the synthesis of 3-amino-9-arylsubstituted-thieno[3,2-b]benzothiazine S,S-dioxide 2-decarboxylated is reported. Thieno-[3,2-b]benzothiazine S,S-dioxide derivatives were investigated for their abilities to inhibit β-hematin formation, hemoglobin hydrolysis and in vivo for their efficacy in rodent Plasmodium berghei. Compounds 5j-o were the most promising as inhibitors of hemoglobin hydrolysis, however, the compounds are not as efficient as chloroquine. A structure-activity relationship (SAR) study was carried out in this series. Our results allow us to determine the minimal structural requirements to produce the biological response.